Assessment of the contribution of calcium and vitamin D in the diet of the elderly - Samolińska, Wioletta; Kiczorowska, Bożena; Klebaniuk, Renata (Polish Journal of Public Health, 2019)
Introduction. The rate of aging and the possible coexistence of diet-related diseases are largely determined by the nutrition and lifestyle of the elderly. Therefore, it is important to assess the degree of coverage of organism demand for such nutrients as calcium and vitamin D in the elderly population. Aim. The aim of the study was to determine the impact of age on calcium and vitamin D supply in daily alimentary rations of the elderly as well as their nutritional behaviour in terms of consumption of products which are the source of these nutrients. Material and methods. The study involved 42 subjects aged from 60 to 85 years. The vitamin D and calcium content in daily food rations was assessed with the method of a 24-hour dietary interview carried out in triplicate. Results. The nutrition of the elderly turned out to be inappropriate in terms of supplying the organism with calcium and vitamin D, and this was not age dependent. The average calcium and vitamin D supply in the daily food rations was estimated at 455.53 mg/day and 2.31 μg/day, respectively. The demand for calcium was covered in the range of 31-60% of RDA in over 60% of the elderly and the vitamin D demand was met in 30% of AI in over 80% of the subjects. Conclusions. The assessment of the daily food rations indicates a necessity for increasing the intake of calcium- and vitamin D-rich food products and dietary supplementation with these components